Mengenal Ekonometri sebagai Alat Analisis Ekonomi yang Kuat - Rahma Nur Hidayah; Kula Khusnihita; Gustina Masitoh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Econometrics is a discipline in economics that combines economic theory, mathematics, and statistics to quantitatively assess economic phenomena. This paper aims to introduce econometrics as an important tool in economic analysis and explain its applications in various sectors such as macroeconomics, microeconomics, development, and finance. Using a descriptive qualitative research method based on literature review, this paper explains how econometrics is used to test economic conjectures, make predictions, and support data-driven decisions. In addition, this article also discusses the advantages of econometrics, the challenges that arise in its application, and the software used in econometric analysis, including Excel, SPSS, and EViews. The findings show that econometrics is useful not only for academics but also for decision makers and business actors in designing more efficient economic strategies and policies. However, several problems such as data limitations, model assumptions, and specification errors are still challenges that need to be overcome by increasing capabilities and utilizing technology. It is hoped that this paper can broaden understanding and encourage more effective and appropriate use of econometrics in Indonesia.